3D‐e‐Chem: Structural Cheminformatics Workflows for Computer‐Aided Drug Discovery. (14th February 2018) - Kooistra, Albert J.; Vass, Márton; McGuire, Ross; Leurs, Rob; de Esch, Iwan J. P.; Vriend, Gert; Verhoeven, Stefan; de Graaf, Chris
Abstract: eScience technologies are needed to process the information available in many heterogeneous types of protein–ligand interaction data and to capture these data into models that enable the design of efficacious and safe medicines. Here we present scientific KNIME tools and workflows that enable the integration of chemical, pharmacological, and structural information for: i) structure‐based bioactivity data mapping, ii) structure‐based identification of scaffold replacement strategies for ligand design, iii) ligand‐based target prediction, iv) protein sequence‐based binding site identification and ligand repurposing, and v) structure‐based pharmacophore comparison for ligand repurposing across protein families. The modular setup of the workflows and the use of well‐established standards allows the re‐use of these protocols and facilitates the design of customized computer‐aided drug discovery workflows. Abstract : Reusable structural cheminformatics for drug discovery: Data analytics platforms such as KNIME enable the creation of robust cheminformatics protocols that can easily be transferred, reused, and extended. 3D‐e‐Chem provides a set of KNIME nodes and reconfigurable workflows for data‐driven drug discovery including: ligand‐based target prediction, structure‐based bioactivity data mapping and ligand scaffold replacement, and ligand repurposing.